PROSPEK LEMBAGA KEUANGAN MIKRO SYARIAH DALAM MENDUKUNG PEMBIAYAAN USAHA BERSKALA MIKRO UNTUK PENGENTASAN KEMISKINAN DI INDONESIA - Lasmiatun - (DHARMA EKONOMI, 2013)
Syariah microfinance institution for micro enterprises, especially Baitul Maal wat Tamwil (BMT) have the good future prospect in Indonesia because its potential. This form of microfinance institution have two functiona, social function and bussiness function. Elaboration of this, must be supported by government so that its role be more strong at public society, and be able to help government for increasing the level of society welfare.Keyword : Baitul Maal wat Tamwil (BMT), prospek, potensi, kesejahteraan, Indonesia